Pengaruh Narsisme CEO, Kepemilikan Asing Dan Keputusan Investasi Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Oktavia, Weri; Susanti, Septria (Shafin: Sharia Finance and Accounting Journal, 2024)
Abstract: This research is motivated by the fact that manufacturing companies listed on the Indonesian Stock Exchange are experiencing low financial performance and are at risk for the company's survival. This research is a quantitative study which aims to find out the influence of CEO narcissism, foreign ownership and investment decisions on the financial performance of manufacturing companies listed on the BEI in 2018-2022. The data collection technique uses a purposive sampling technique with secondary data types and sources obtained from financial reports via the official website of the Indonesia Stock Exchange. The data analysis technique used is multiple linear regression analysis processed using SPSS 24. The results of this study show that CEO narcissism does not have a significant effect on financial performance. Foreign ownership has a positive and significant effect on financial performance. Then investment decisions have a negative and significant effect on financial performance. The research results simultaneously show that CEO narcissism, foreign ownership and investment decisions have a positive and significant effect on corporate financial performance in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Keywords: CEO narcissism; Foreign Ownership; Investationdecision; Financial performance